2005
DOI: 10.1017/s0950268805004681
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's disease in people exposed to clinical cases of bovine paratuberculosis

Abstract: Mycobacterium avium subspecies paratuberculosis (Map), the cause of ruminant paratuberculosis, has been proposed as the causative agent of Crohn's disease. The objective of this study was to determine whether exposure to clinical cases of bovine paratuberculosis was a risk factor for Crohn's disease. A questionnaire was sent to dairy farmers living on premises where the occurrence or absence of clinical cases of bovine paratuberculosis had previously been determined. The prevalence of Crohn's disease was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 37 publications
2
30
0
1
Order By: Relevance
“…(Sakamoto et al, 2005;Maconi et al, 2010) Mushrooms NS: 347/1/1 (Sakamoto et al, 2005) Fruit 0.78 (0.7, 0.87): 218/1/1 NS: 532/2/2 (Sakamoto et al, 2005;Abubakar et al, 2007;Maconi et al, 2010) Bread NS: 532/2/2 (Sakamoto et al, 2005;Maconi et al, 2010) Grains 0.51 (0.27. 1) -bran 0.38 (0.21, 0.7)-oat 0.2 (0.1, 0.38) -rye 217/1/1 NS: 185/1/1 (Van Kruiningen et al, 2005;Maconi et al, 2010) Rice NS: 532/2/2 (Sakamoto et al, 2005;Maconi et al, 2010) Pasta NS: 532/2/2 (Sakamoto et al, 2005;Maconi et al, 2010) Nuts and Seeds NS: 347/1/1 (Sakamoto et al, 2005) Oil NS: 185/1/1 (Maconi et al, 2010) Butter/ margarine NS: 185/1/1 (Maconi et al, 2010) Fats 2.64 (1.29, 5.39) * :347/1/1 (Sakamoto et al, 2005) Sugar 2.12 (1.08, 4.17) * :347/1/1 (Sakamoto et al, 2005) sweets/ confections NS: 185/1/1 2.83 (1.38, 5.83): 347/1/1 (Sakamoto et al, 2005;Maconi et al, 2010) soft drink consumption 0.68 (0.44, 1.04): 797/1/1 (Bernstein et al, 2006) Coffee/Tea consumption NS: 5361/1/1 (Jones et al, 2006) Filtered Water 0.45 (0.27, 0.76): 218/1/1 (Abubakar et al, 2007) Public Water supply (Qual et al, 2010) Occupation: veterinarian NS: 1526/1/1 (Qual et al, 2010) living on a farm 0.69 (0.44, 1. (Jones et al, 2006;Abubakar et al...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Sakamoto et al, 2005;Maconi et al, 2010) Mushrooms NS: 347/1/1 (Sakamoto et al, 2005) Fruit 0.78 (0.7, 0.87): 218/1/1 NS: 532/2/2 (Sakamoto et al, 2005;Abubakar et al, 2007;Maconi et al, 2010) Bread NS: 532/2/2 (Sakamoto et al, 2005;Maconi et al, 2010) Grains 0.51 (0.27. 1) -bran 0.38 (0.21, 0.7)-oat 0.2 (0.1, 0.38) -rye 217/1/1 NS: 185/1/1 (Van Kruiningen et al, 2005;Maconi et al, 2010) Rice NS: 532/2/2 (Sakamoto et al, 2005;Maconi et al, 2010) Pasta NS: 532/2/2 (Sakamoto et al, 2005;Maconi et al, 2010) Nuts and Seeds NS: 347/1/1 (Sakamoto et al, 2005) Oil NS: 185/1/1 (Maconi et al, 2010) Butter/ margarine NS: 185/1/1 (Maconi et al, 2010) Fats 2.64 (1.29, 5.39) * :347/1/1 (Sakamoto et al, 2005) Sugar 2.12 (1.08, 4.17) * :347/1/1 (Sakamoto et al, 2005) sweets/ confections NS: 185/1/1 2.83 (1.38, 5.83): 347/1/1 (Sakamoto et al, 2005;Maconi et al, 2010) soft drink consumption 0.68 (0.44, 1.04): 797/1/1 (Bernstein et al, 2006) Coffee/Tea consumption NS: 5361/1/1 (Jones et al, 2006) Filtered Water 0.45 (0.27, 0.76): 218/1/1 (Abubakar et al, 2007) Public Water supply (Qual et al, 2010) Occupation: veterinarian NS: 1526/1/1 (Qual et al, 2010) living on a farm 0.69 (0.44, 1. (Jones et al, 2006;Abubakar et al...…”
mentioning
confidence: 99%
“…1) -bran 0.38 (0.21, 0.7)-oat 0.2 (0.1, 0.38) -rye 217/1/1 NS: 185/1/1 (Van Kruiningen et al, 2005;Maconi et al, 2010) Rice NS: 532/2/2 (Sakamoto et al, 2005;Maconi et al, 2010) Pasta NS: 532/2/2 (Sakamoto et al, 2005;Maconi et al, 2010) Nuts and Seeds NS: 347/1/1 (Sakamoto et al, 2005) Oil NS: 185/1/1 (Maconi et al, 2010) Butter/ margarine NS: 185/1/1 (Maconi et al, 2010) Fats 2.64 (1.29, 5.39) * :347/1/1 (Sakamoto et al, 2005) Sugar 2.12 (1.08, 4.17) * :347/1/1 (Sakamoto et al, 2005) sweets/ confections NS: 185/1/1 2.83 (1.38, 5.83): 347/1/1 (Sakamoto et al, 2005;Maconi et al, 2010) soft drink consumption 0.68 (0.44, 1.04): 797/1/1 (Bernstein et al, 2006) Coffee/Tea consumption NS: 5361/1/1 (Jones et al, 2006) Filtered Water 0.45 (0.27, 0.76): 218/1/1 (Abubakar et al, 2007) Public Water supply (Qual et al, 2010) Occupation: veterinarian NS: 1526/1/1 (Qual et al, 2010) living on a farm 0.69 (0.44, 1. (Jones et al, 2006;Abubakar et al, 2007;Qual et al, 2010) JD on the farm 1.63 (0.15, 9.95): 5361/1/1 (Jones et al, 2006) Animal density in water catchment NS: 218/1/1 (Abubakar et al, 2007) JD in water catchment NS: 218/1/1 (Abubakar et al, 2007) CD: Crohn's disease, JD: Johne's disease, NS: not significant, OR odds ratio, CI: confidence interval, * high calorie consumer, ~ low calorie consumer, ^ odds of being M. paratuberculosis ELISA positive.…”
mentioning
confidence: 99%
“…Jones et al concluded "The prevalence of Crohn's disease was found to be similar to that reported in other studies in the United Kingdom and showed no association with bovine paratuberculosis." 18 There was no greater frequency of CD in farmers with daily exposure to cattle that were shedding MPTB than in those with herds that were culturenegative. Qual et al recently supported this lack of association in their study of the frequency of Crohn's disease in producers and veterinarians exposed to dairy and beef herds infected with MPTB.…”
Section: Bacteriologic Culturementioning
confidence: 90%
“…First, farmers (and persons in rural settings) should be at increased risk of a livestockassociated pathogen, yet there is no evidence that they have increased rates of CD [42] . Second, environmental conditions, such as poor sanitation and overcrowding which should favor transmission of an infection, actually appear to protect against CD.…”
Section: Epidemiologic Evidence For Map As a Cause Of CDmentioning
confidence: 99%